A systematic review and analysis of medication education for medication misuse in children - Dewangan, Hemlata; Nirmal Chandu, Himanshu (Journal of Neonatal Surgery, 2025)
The research carefully assessed evidence of educational strategies concerning prescription and nonprescription drugs for kids in school. Search criteria concentrated on demographic schooling, kids in school, and pharmaceuticals. Research was omitted if it pertained to a specific illness state, type of drugs, substances of misuse, or illegal substances. The data extraction encompassed study design, position, educational treatment and time frame, study techniques, and principal findings. The research identified 15 studies corresponding to 9 distinct programs. Six initiatives were recognized in the gray research. Projects varied from solitary sessions to nationwide initiatives. Quantitative research demonstrated enhancements in understanding, medicine literacy, and trust. Implementing medication teaching initiatives relied on the educator's confidence and convictions about the security of medications. Reliable pharmaceutical education options exist and have demonstrated an enhancement in knowledge among learners. A necessity persists for comprehensive implementation and assessment strategies. Methods and resources exist to execute initiatives within neighborhoods to enhance medication education among kids. Structures ought to be employed to improve the execution of successful health promotion programs regarding prescription drugs for pupils in school.